PENGARUH MODAL MINIMAL, PENGETAHUAN INVESTASI DAN PRESEPSI RISIKO INVESTASI TERHADAP MINAT INVESTASI MAHASISWA DI PASAR MODAL - Silvia Hendrayanti; Paramitha Dyan Shavira (Sekolah Tinggi Ilmu Ekonomi Semarang, 2023)
There are many things that can affect students' investment interest from various factors, such as minimal capital, investment knowledge and risk perception. The purpose of this study was to determine the minimum capital factors, investment knowledge and risk perceptions that influence STIE Semarang students' interest in investing in the capital market. In this study, researchers used quantitative analysis methods and for sampling in this study used a purposive sampling technique using the entire population of 46 STIE Semarang students. From the results of data processing, it is obtained that the t test on minimum capital has a significance value of 0.031 <0.050, meaning that the minimum capital variable has a positive and significant effect on investment interest. The investment knowledge variable has a significance value of 0.118 > 0.050, meaning that the investment knowledge variable has a positive and insignificant effect on investment interest. And the risk perception variable has a significance value of 0.038 <0.050, meaning that the risk perception variable has a positive and significant effect on investment interest. From the research results, the results of the F test were 24.664 > 2.83 with a significance value of 0.000 <0.050. Suggestions for campuses and investment galleries, namely, are expected to increase knowledge and provide education to students regarding investment knowledge in order to attract student investment interest